Region and layer-specific expression of GABAA receptor isoforms and KCC2 in developing cortex - Zavalin, Kirill; Hassan, Anjana; Zhang, Yueli; Khera, Zain; Lagrange, Andre H. (Frontiers in Cellular Neuroscience, 2024)
Introduction γ-Aminobutyric acid (GABA) type A receptors (GABAARs) are ligand-gated Cl-channels that mediate the bulk of inhibitory neurotransmission in the mature CNS and are targets of many drugs. During cortical development, GABAAR-mediated signals are significantly modulated by changing subunit composition and expression of Cl-transporters as part of developmental processes and early network activity. To date, this developmental evolution has remained understudied, particularly at the level of cortical layer-specific changes. In this study, we characterized the expression of nine major GABAAR subunits and K-Cl transporter 2 (KCC2) in mouse somatosensory cortex from embryonic development to postweaning maturity. Methods We evaluated expression of α1-5, β2-3, γ2, and δ GABAAR subunits using immunohistochemistry and Western blot techniques, and expression of KCC2 using immunohistochemistry in cortices from E13.5 to P25 mice. Results We found that embryonic cortex expresses mainly α3, α5, β3, and γ2, while expression of α1, α2, α4, β2, δ, and KCC2 begins at later points in development; however, many patterns of nuanced expression can be found in specific lamina, cortical regions, and cells and structures. Discussion While the general pattern of expression of each subunit and KCC2 is similar to previous studies, we found a number of unique temporal, regional, and laminar patterns that were previously unknown. These findings provide much needed knowledge of the intricate developmental evolution in GABAAR composition and KCC2 expression to accommodate developmental signals that transition to mature neurotransmission.